Puti issledovanija i realizacii differencirovannogo podchoda v sisteme podgotovki junych sportsmenov - Kvasuk, P. V. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The key direction of the perfection of the strategy of elite athletes training in the modern conditions of development of Olympic sports is the individualization of training process at stages of becoming of sports skill. But at the discussion of the problem of the perfection of the system of of young athletes, preparation it is more correct to speak about the differentiated approach to construction of training process instead of the individual one. The essence of the differentiated approach In the literature on the general and sports pedagogics is defined by the combination of collective and individual forms of training that allows to organize the process of training of children and teenagers according to their typical and specific features. The further progress of perfection of system of young athletes training is connected with the scientific development of theoretical-methodological and technological aspects of realization of the individual-differentiated approach at stages of long-term training.